Collaborative Social Studies Learning Through Exploration: The Use of Google Maps as a STEAM-Based Learning Media - Rahmawati, Melinda; Kusumo, Dwi Ananto; Pratiwi, Adinda; Qodariah, Lelly (Program Studi Pendidikan IPS, 2024)
This study aims to present a collaboration between scouting education through exploration activities and social studies learning through the use of the google maps application as a STEAM-based learning medium. Innovation in social studies learning activities must continue to be expanded, especially with rapid social changes that also have an impact on the rapid changes in the learning models and methods implemented. Including collaborating with non-formal educational institutions, one of which is the Scout Movement. Through collaborative and actual learning activities, it can become a new learning style that can develop collaboration, communication, critical thinking, and creativity skills. The method used to study this used explanatory qualitative through literature studies. Thus, the results of this study show that the use of google maps can also be a collaborative learning medium in social studies learning through exploration activities in scouting education. Social studies learning, which contains the content of geography material, can be the main guideline in knowing and studying spatial changes to the patterns of social interaction of the community.